A robot for non-destructive testing weld inspection of offshore mooring chains. (9th May 2018) - Hernandez, A; Altuzarra, O; Petuya, V; Pinto, Ch; Amezua, E
Welding flaw detection is a key step in manufacturing many components. In offshore chains, every link is manufactured from a steel bar that is bent and the ends joined by flash butt welding. Ultrasonic inspection of the welded area is required for classification. Defects, if any, are parallel to the welded area, which do not favour detection by manual inspection with 45° beams, as per usual practice . This article reports on CIRUS, a robot developed for automatic inspection of the weld area using a combination of pulse-echo and pitch-catch ultrasonic testing. The robot kinematic structure includes global positioning, local positioning and inspection subsystems, and each subsystem design is described in detail. A data acquisition system processes ultrasonic inspection results and provides visual information for the inspector as well as traceability for quality manufacturing.